Christmas angel [videorecording (DVD)] - Brough, Brian; Hawker, Kari; Davison, Bruce, 1946- (SunWorld Pictures, 2009)
Ashley feels alone this Christmas as she searches fruitlessly for a job. But her neighbor Nick knows exactly what to do. He offers her a job to be his assistant in the best work of all, helping others. There is only one catch. Ashley cannot tell anyone her new boss is a Secret Santa. Can she keep her big secret from her new, but nosey reporter boyfriend?